2014
DOI: 10.1007/s10562-014-1434-y
|View full text |Cite
|
Sign up to set email alerts
|

Heteroatom-Doped Carbon Nanostructures as Oxygen Reduction Reaction Catalysts in Acidic Media: An Overview

Abstract: This paper provides an overview of the studies that were conducted in our laboratories in the last decade on hetero-atom doped carbon structures as potential oxygen reduction reaction (ORR) catalysts for PEM fuel cells. These studies include evaluating the potential of nitrogen doped carbon nanostructures as cathode catalysts for proton exchange membrane and direct methanol fuel cells and examining the nature of the transition metal used as growth catalysts in synthesis of these materials, through activity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 50 publications
1
48
0
1
Order By: Relevance
“…X‐ray photoelectron spectroscopy (XPS) can be used to evaluate the surface oxygen content attributable to the reactions of carbon oxidation. Hydroquinone/quinone system is an indicator of carbon corrosion, and with negligible increase of current for hydroquinone/quinone peaks at 0.6 V versus RHE with high‐voltage holds means that the catalyst is resistant to carbon corrosion . This test could be conducted to monitor the carbon corrosion on a porous carbon electrode surface.…”
Section: Best Practice For Oxygen and Hydrogen Electrocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…X‐ray photoelectron spectroscopy (XPS) can be used to evaluate the surface oxygen content attributable to the reactions of carbon oxidation. Hydroquinone/quinone system is an indicator of carbon corrosion, and with negligible increase of current for hydroquinone/quinone peaks at 0.6 V versus RHE with high‐voltage holds means that the catalyst is resistant to carbon corrosion . This test could be conducted to monitor the carbon corrosion on a porous carbon electrode surface.…”
Section: Best Practice For Oxygen and Hydrogen Electrocatalysismentioning
confidence: 99%
“…[152] Carbons at the edges are found to be more active for ORR, compared to those near basal planes. [153] Particularly Adv. Energy Mater.…”
Section: Heteroatom Doping Defects and Hybridizationmentioning
confidence: 99%
“…In many cases, the pyrolysis results not only in the formation of the FeC x N y and/or FeN x moieties but also in the formation of Fe, Fe 3 N, and Fe 3 C nanoparticles . The FeC x N y and/or FeN x moieties located at the surface carbon scaffold as well as the Fe, Fe 3 N, and Fe 3 C nanoparticles are generally deemed as the active sites for ORR …”
Section: Introductionmentioning
confidence: 99%
“…synthesized a Fe‐based non‐PGM ORR electrocatalyst with a MOF support and suggested that Fe first plays a catalytic role during the heat treatment to form the graphitized structure of N‐doped carbon, while some Fe blends into the carbon and improves the electrocatalytic properties of catalyst, thus facilitating the 4e − reduction of oxygen. With a better understanding of the catalytically active species and the mechanism of oxygen reduction, researchers working on M−N−C catalysts are much more focused on increasing the efficient active sites …”
Section: Introductionmentioning
confidence: 99%
“…With a better understanding of the catalytically active species and the mechanism of oxygen reduction, researchers working on MÀNÀC catalysts are much more focused on increasing the efficient active sites. [15][16][17][18] The specific surface area and the nitrogen content of catalysts are two of the most important factors affecting the formation of active sites. At present, one of the effective methods is to regulate the specific surface area and pore size of the catalyst and thus expose more active sites.…”
Section: Introductionmentioning
confidence: 99%